IMMUNOENDOCRINOLOGY ASSOCIATION OF TOXOPLASMA GONDII AND THYROID HORMONES IN IRAQI PATIENTS WITH CLINICAL MANIFESTATIONS OF TOXOPLASMOSIS - ALI IBRAHIM ALI AL-EZZY; WALAA NAJM ABOOD (International Journal of Pharma and Bio Sciences, 2016)
The aim is to determine the correlation among age, gender; thyroid hormones and anti T.gondii antibodies. Anti T.gondii antibodies; TSH, T3, T4 serum level evaluated by ELISA technique in 113 Iraqi patients. Anti T.gondii Immunoglobulines correlated with gender, T.gondii IgM inversely correlated with male gender and positively with male age groups. No significant correlation between IgM, IgG positivity and TSH levels. T.gondii IgM positive /negative correlated with T3 among females. IgM positive males have elevated T4 (0.88%) v (6.19%) for females. T.gondii specific IgM positive /negative inversely correlated with T4 among females T.gondii IgM, IgG positive responses significantly associated with gender. T3, T4 inversely correlated with anti T.gondii IgM positive response among females. Increase in T3 and T4 thyroid hormones production in toxoplasmosis, provide new clue to the complex pathogenesis of Toxoplasma-associated thyroid diseases.